Surgical Management Of Post-Traumatic Facial Asymmetry: Systematic Overview Of Techniques, Outcomes, And Patient Satisfaction - Dandoulakis, Emmanouil (Journal of Neonatal Surgery, 2025)
Facial asymmetry that occurs post-trauma is a serious aesthetic and functional issue and can be caused by either the fractures, the injuries in the soft tissues, or malunion. This systematic review examines surgical management methods, clinical outcomes, and patient satisfaction to provide evidence-based information for optimizing treatment. In line with the PRISMA recommendations, we identified peer-reviewed studies on the surgical treatment of post-traumatic facial asymmetry by searching PubMed, Scopus, Web of Science, and the Cochrane Library (2010-2025). Information was retrieved regarding methods (e.g., osteotomies, bone grafting, tissue reconstruction), objective outcome measures (e.g., symmetry indices, functional outcomes), complications, and subjective outcome measures (e.g., FACE-Q scores). The quality was evaluated using the Newcastle-Ottawa Scale and the Cochrane Risk of Bias tools. The results showed that bony reconstruction, which also includes computer-assisted osteotomies and 3D-printed guides, is associated with a high degree of symmetry restoration but also carries risks such as infection or implant failure. The soft tissue techniques, including fat grafting and flaps, aimed at enhancing beauty, however, often show unpredictable long-term results. Functional restoration and aesthetic perfection have a high interrelation with patient satisfaction, although standardized outcomes are hardly used. Significant gaps exist in the scant long-term follow-up and the lack of data on the pediatric and geriatric populations. More novel technologies, such as surgical planning and regenerative procedures, are exciting, even more so. The review contributes to specifying the need for patient-centered, evidence-based measures and identifies areas of research that could be examined in the future. The results of such findings are expected to inform clinicians in the process of personalizing interventions, aid in conducting high-impact studies, and enhance the effectiveness of facial asymmetry management outcomes in post-traumatic stress.